The Opposition between Instrumental and Lusory Rationality in the Utopian Proposal of Bernard Suits - López Frías, Francisco Javier; Gimeno Monfort, Xavier (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
In this paper, we explore Bernard Suits’ analysis of the instrumental use of reason in the utopia presented in The Grasshopper. To do so, we analyze the role instrumental rationality plays in Suits’ theory of games and utopia. Then, we compare the use of instrumental reason to what we call «lusory rationality.» The latter embodies the lusory attitude that players have to adopt to play a game and live in Suits’ Utopian world. To conclude, we argue that the lusory attitude offers an alternative to the predominance of the instrumental use of reason in our society.